An implicit multistep block method for fuzzy differential equations - Ramli, Azizah; Abdul Majid, Zanariah (IEEE, 2015)
A 2-point diagonally implicit multistep block method of order five is proposed. It is implemented to find the approximation for first-order fuzzy differential equations (FDEs) under on Seikkala derivative. This block method operates by approximating two points at yn+1 and yn+2 concurrently in a step. Both formulas are derived by using Lagrange interpolating polynomial. The method is generated by combining the predictor and corrector formulas in the PE(CE)m mode, where m is the number of iteration. The performances of the method are illustrated by solving problem and the numerical findings are compared with the existing method.